Therapeutic Options Against the New Coronavirus: Updated Clinical and Laboratory Evidences - Fernandes, Amélia C.; Vale, Adson J.; Guzen, Fausto P.; Pinheiro, Francisco I.; Cobucci, Ricardo N.; de Azevedo, Eduardo P. (Frontiers in Medicine, 2020)
The pandemic caused by the new coronavirus (SARS-Cov-2) has encouraged numerous in vitro studies and clinical trials around the world, with research groups testing existing drugs, novel drug candidates and vaccines that can prevent or treat infection caused by this virus. The urgency for an effective therapy is justified by the easy and fast viral transmission and the high number of patients with severe respiratory distress syndrome who have increasingly occupied intensive care hospital beds, leading to a collapse in health systems in several countries. However, to date, there is no sufficient evidence of the effectiveness of any researched therapy. The off-label or compassionate use of some drugs by health professionals is a reality in all continents, whose permission by regulatory agencies has been based on the results of some clinical trials. In order to guide decision-making for the treatment of COVID-19, this review aims to present studies and guidelines on the main therapies that have been and are currently being tested against SARS-Cov-2 and to critically analyze the reported evidences.